Variation in the mating system of Vincetoxicum hirundinaria (Asclepiadaceae) in peripherial island populations. - Leimu, R (2004)
BACKGROUND AND AIMS: Self-fertility may be selected for in small and isolated plant populations of normally outcrossing species. In addition, adaptations for self-fertility are likely to arise in island populations and in populations that are located at the border of the species range. The mating system of Vincetoxicum hirundinaria (Asclepiadaceae) is examined in island populations that are located at the northern border of the species range. METHODS: Pollination experiments were conducted under glasshouse conditions with plants from four populations. KEY RESULTS: The frequencies of self-fertile individuals were relatively high and did not differ among populations. Cross-pollination resulted in higher fruit set than self-pollination. However, fruit-set from self-pollination and cross-pollination did not differ in the self-fertile individuals. Interestingly, the proportion of aborted fruits was on average higher following cross-pollination than following self-pollination. No differences were observed in seed number or seed mass between self- and cross-pollinated fruits. Pollen tube growth following self- and cross-pollinations was indistinguishable. CONCLUSIONS: The results of this study revealed that V. hirundinaria possess a mixed-mating system in the studied island populations. Evidence was also provided for a late-acting self-incompatibility system commonly observed in Asclepiadaceae. No clear signs of inbreeding depression were observed in the early stages of development.